LANSCAPE SELF LOVE: Edukasi Seksualitas dan Edukasi Self-Love pada Siswa Sekolah Dasar Melalui E-Comic: LANSCAPE SELF LOVE: Sexuality Education and Self-Love Education for Elementary School Students Through E-Comics - Hidajat, Helga Graciani; Putri, Raissa Dwifandra; Putri, Paramytha Magdalena Sukarno; Novianti, Ranti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
One of the developmental tasks of elementary school students is to be able to care for their sexual and mental health. The empirical problem faced by students at SD Negeri Mergosono 03 is that elementary school students do not yet have an understanding of sexual health, plus the challenge of adapting to body changes due to puberty and other sexuality problems. Mergosono 03 Public Elementary School students also have the problem of low self-love, characterized by feelings of inferiority, and difficulty accepting their strengths and limitations. Sexuality and mental health education related to self-love is still not found in this school. Partners also need this education. Therefore, the proposer developed the LANSCAPE SELF LOVE program: Sexuality education and self-love education for elementary school students through e-comics to address partners' problems and needs. This program is carried out through 4 stages: e-comic development, sexuality education, self-love education, and the dynamics of self-analysis related to self-strengths and limitations. This community service can increase students' understanding of sexuality and mental health.